Юридичні аспекти правовідносин у сфері трансплантології органів та тканин людини - Коренга, Ю.; Korenga, Iu. (Східноєвропейський національний університет імені Лесі Українки, 2015)
Дослідження присвячене юридичним аспектам відносин з трансплантації як однієї з найбільш новітньої галузі медицини. Розглядаються такі приватнотрансплантологічні правові проблеми, як констатація смерті мозку потенційного донора при збереженні кровообігу і життєздатності, проблема відключення засобів підтримання життя, вирішення питання про право особи розпоряджатися своїм тілом і органами після смерті. Дається характеристика правовим відносинам, які виникають при трансплантації. Розглядається питання видів трансплантації. Проведено детальне дослідження таких принципів правового регулювання трансплантації, як принцип допустимої шкоди, принцип поваги і дотримання прав пацієнта. Виділено дві моделі регулювання донорства органів і тканин від померлих. The research is devoted to legal aspects of relations in the field of transplantation as one of the most effectively developing branch of medicine. The article sheds the light on private transplantological legal problems such as a statement of brain death of a potential donor while maintaining blood flow and viability of the act of turning off life support means, solving the problem of the right of the individual to dispose his own body and organs after death. The characteristics of the legal relations arising in the transplantation and the kinds of transplantation are in the focus of attention in the article. The author presents a detailed study of the principles of legal regulation of transplantation, such as permissible harm principle, the principle of respect to and observance of the rights of the patient. The article places importance on two regulatory models of organ donation and tissues from deceased, so-called «presumption of consent» and «presumption of disagreement». This work is an attempt to examine the shortcomings of the current regulatory framework in the field of transplantation, which the doctors and patients face during the operation.
Legal Aspects of Relations in the Field of Transplantation of Human Organs and Tissues
Keywords: медичне право; трансплантація; презумпція згоди; презумпція незгоди; реципієнт; донор; medical law; transplantation; the presumption of consent; the presumption of disagreement; the recipient; the donor